(untitled) (Communications in Computational Physics, 2006)
This paper is concerned with the numerical simulation of multiphase, multicomponent flow in porous media. The model equations are based on compositional flow with mass interchange between phases. The compositional model consists of Darcy's law for volumetric flow velocities, mass conservation for hydrocarbon components, thermodynamic equilibrium for mass interchange between phases, and an equation of state for saturations. High-accurate finite volume methods on unstructured grids are used to discretize the model governing equations. Special emphasis is placed on studying the influence of gravitational effects on the overall displacement dynamics. In particular, free and forced convections, diffusions, and dispersions are studied in separate and combined cases, and their interplays are intensively analyzed for gravitational instabilities. Extensive numerical experiments are presented to validate the numerical study under consideration.